A provider's approach to the assurance market of sustainability reports in Spain - Natalia Vaz Ogando; Silvia Ruiz Blanco; Belen Fernandez-Feijoo (Administrative Sciences, 2018)
The assurance of sustainability reports faces significant challenges that arise from the characteristics of sustainability information and the regulatory context in which it is developed. This recently growing service has favoured the creation of a rapidly evolving market, a complex professional field in its early stages of development and study. The aim of this paper is to analyse whether the use of international standards or the profile of the provider performing the service affects assurance process and quality. To this end, we applied a novel methodology for this field: a survey through written questionnaires. The use of a primary information source allows us to gain insight into the topic, beyond other visible aspects often used in previous literature (e.g., assurance statement contents). We tested our hypotheses on a sample of Spanish accounting and consulting firms. Our results show that neither the use of international standards nor the provider's professional background has any effect on assurance process and assurance quality. However, the way the professional perceives the developed service does have an impact on quality.
Keywords: 350; assurance; sustainability reports; assurance providers; market; assurance process; quality